Instituciones informales y actividad emprendedora: Una aproximación metodológica desde D. North (2010)
The purpose of this work is to reflect upon the methodological pertinence of assuming the theoretical approach of informal institutions as a tool to delve into the study of entrepreneurial activity. We sustain the validity of using the particularistic ethnographic approach as a tool that allows understanding the entrepreneurial phenomenon from the perspective of its actors. By taking on the guiding question of: How far do informal institutions such as family, friends and personal contacts, have an impact on entrepreneurial activity? We conclude that cultural values are the mediation between individuals and their social environment in which the beliefs,behaviors and personal motivation constitute the essential aspects to understand entrepreneurial activity.